2021
DOI: 10.1371/journal.pone.0258344
|View full text |Cite
|
Sign up to set email alerts
|

Connection, constraint, and coping: A qualitative study of experiences of loneliness during the COVID-19 lockdown in the UK

Abstract: The COVID-19 pandemic has necessitated physical distancing which is expected to continue in some form for the foreseeable future. Physical distancing policies have increased reliance on digital forms of social connection and there are widespread concerns about social isolation and mental health in this context. This qualitative study sought to understand how loneliness was experienced during physical distancing in the initial national UK COVID-19 lockdown. Eight individuals who reported feeling lonely during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 58 publications
1
50
0
1
Order By: Relevance
“…McKenna‐Plumley et al. ( 2021 ) suggested this may be a result of a loss of in‐person interaction, and a loss of freedoms. Some scholars have suggested that the pandemic may have had a worse effect on women's loneliness (Jones et al., 2021 ; Wickens et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McKenna‐Plumley et al. ( 2021 ) suggested this may be a result of a loss of in‐person interaction, and a loss of freedoms. Some scholars have suggested that the pandemic may have had a worse effect on women's loneliness (Jones et al., 2021 ; Wickens et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of research into gendered experiences of loneliness during the pandemic. McKenna‐Plumley et al.’s ( 2021 ) study included just two men, and larger scale statistical studies of prevalence do not capture the context of the aggregate sex difference they present. If men are disinclined to acknowledge loneliness, how might that be understood and enacted in a pandemic situation in which loneliness has become a significantly greater concern?…”
Section: Introductionmentioning
confidence: 99%
“…For example, frequent social interactions and talking with other people are both associated with greater well-being [ 10 ]. Despite this, empirical evidence on the psychological, behavioural and social effects of the pandemic and the consequences for mental health, especially in the workplace, is sparse [ 12 14 ]. This is striking given that the workplace is considered to be one of the most important environments to affect mental health [ 15 ] and social isolation and loneliness have become widely recognised as workplace stressors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, empirical evidence on the psychological, behavioural and social effects of the pandemic and the consequences for mental health, especially in the workplace, is sparse [9][10][11]. This is striking given that the workplace is considered to be one of the most important environments to affect mental health [12] and recent studies suggest that the likelihood and duration of insufficient social relationships may be greater in the workplace than in personal life [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the mental health consequences of earlier epidemics and pandemics is sparse, and the extent and duration of the measures to contain COVID-19 are unprecedented [15]. In the context of the nationwide measures across most of the world, policymakers and researchers have raised concerns that people will experience prolonged social isolation [9, 16, 17], which can be defined as the absence or limitation of social connections [18]. Even though social isolation itself is associated with morbidity, related research suggests that mental health is less influenced by the objective absence of social connections than by the perceived discrepancy between actual and desired connections [16, 19].…”
Section: Introductionmentioning
confidence: 99%